The impacts of monetary policy in the 21st century : perspectives from emerging economies - Das, Ramesh Chandra (Emerald Publishing Limited, 2019)
Since the turn of the 21st century, the global economy has faced several significant financial crises such as the monetary mismanagements of the EURO Zone countries struggling with sovereign debt problems, the Global Financial Crisis between 2007 and 2009 preceded by the housing market collapse, and the Quantitative Easing Policies used by the US Central Bank. The Impacts of Monetary Policy in the 21st Century: Perspectives from Emerging Economies explores and analyses how monetary authorities have handled and continue to confront these issues of economic crises at both a global and country-specific level.The book establishes the effect of monetary policies upon economic indicators during the 21st Century at the global, regional, group or country levels, with an emphasis upon emerging economies such as India. In looking at the effects of globalization, demonetization and inflation targeting through the use of panel regression models, unit root tests and case studies, the book provides a unique coverage of quantitative financial economics.The Impacts of Monetary Policy in the 21st Century is an illuminating book for postgraduate-level students, researchers and academics in the fields of economics and finance to help develop their understanding of the severe impact of monetary policies upon global economic systems and emerging economies.
Includes index.
Keywords: Monetary policy -- Developing countries.; Monetary policy -- India.; Economic indicators -- East Asia.; Economic development -- India.; Financial crises.; Business & Economics -- Money & Monetary Policy.; Monetary economics.; elektronické knihy; electronic books